BIOLOGICAL THERAPY OF PSORIASIS - Sivamani, Raja K (Medknow Publications, 2010)
The treatment of psoriasis has undergone a revolution with the advent of biologic therapies, including infliximab, etanercept, adalimumab, efalizumab, and alefacept. These medications are designed to target specific components of the immune system and are a major technological advancement over traditional immunosuppressive medications. These usually being well tolerated are being found useful in a growing number of immune-mediated diseases, psoriasis being just one example. The newest biologic, ustekinumab, is directed against the p40 subunit of the IL-12 and IL-23 cytokines. It has provided a new avenue of therapy for an array of T-cell-mediated diseases. Biologics are generally safe; however, there has been concern over the risk of lymphoma with use of these agents. All anti-TNF-α agents have been associated with a variety of serious and “routine” opportunistic infections.